(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Purpose of the Research: This study aims to examine the impact of demographic factors, consumer awareness, and knowledge, and purchasing behavior on exotic vegetable consumption in Pune city. The escalating interest in exotic vegetables globally necessitates a comprehensive exploration of consumer behavior, which remains under-researched. Methodology: The research utilized a quantitative approach, employing a survey to collect data from a representative sample of 400 consumers actively purchasing exotic vegetables in Pune. The collected data was subjected to analysis using SPSS to derive meaningful insights into consumer behavior patterns. Major Results: The findings of the study reveal that demographic factors, specifically age, income, and education level, significantly influence consumer behavior towards exotic vegetables in Pune city. Additionally, the research highlights a notable consumer awareness regarding the nutritional value and culinary uses of exotic vegetables. This underscores the importance of both demographic factors and consumer knowledge in shaping purchasing behavior.